PENGARUH BIBLIOTERAPI AFEKTIF UNTUK MENURUNKAN AGRESIVITAS SISWA KELAS EMPAT - , DWIE ANGGRAHENI PUSPITASARI; , Dr. Murtini, SU., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Aggressive behaviour among elementary school students is a problem that needs to be attended by various parties. Facts show that name calling between elementary students often lead to physical fights and in some case can cause death. This study aimed to examine effectiveness of Affective Bibliotherapy in reducing aggressive behaviours of fourth grader. Research was carried out on ten male students showing aggressive behaviour at school. Interventions were given to five students as experimental group using Affective Bibliotherapy. Affective Bibliotherapy is an intervention technique based on psychodynamic approach. Affective Bibliotherapy is a therapeutic learning process through written materials. The reading materials given can help children in identifying with existing figure in the story plot, through which children became emotionally engaged. Through this process, children can release the suppressed emotional tensions and gain insight on the problems. Data analysis using Mann-Whitney U-test showed that aggresive behavious was reduced significantly.